2021
DOI: 10.1002/ecs2.3662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of camera‐trap placement and number on detection of members of a mammalian assemblage

Abstract: A central goal in camera-trapping (CT) studies is to maximize detection probability and precision of occupancy estimates while minimizing the number of CTs to reduce equipment and labor costs. Few studies, however, have examined the effect of CT number on detection probability. Moreover, historically, most studies focused on a specific species and the design could be tailored toward maximizing detection of this target species. Increasingly, however, such studies use data for all captured, non-target, species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Missed detections could potentially generate misleading results in camera trapping studies, and therefore, create difficulties as regards direct comparison among studies (Jacobs & Ausband, 2018). In this respect, despite some statistical approaches accounting for the imperfect detection (Guillera-Arroita et al, 2010), recent studies have shown that biased and imprecise results can be obtained when detection probabilities are low (Hofmeester et al, 2021;Kays et al, 2021). Additionally, (1) there are a wide variety of studies that used the raw encounter rates without accounting for false-negatives (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Missed detections could potentially generate misleading results in camera trapping studies, and therefore, create difficulties as regards direct comparison among studies (Jacobs & Ausband, 2018). In this respect, despite some statistical approaches accounting for the imperfect detection (Guillera-Arroita et al, 2010), recent studies have shown that biased and imprecise results can be obtained when detection probabilities are low (Hofmeester et al, 2021;Kays et al, 2021). Additionally, (1) there are a wide variety of studies that used the raw encounter rates without accounting for false-negatives (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our results have greater implications for studies of animal diversity with broad spatial extents in topographically-complex landscapes. Much effort has gone into understanding variability in animal detection at camera-traps (Moll et al 2020, Hofmeester et al 2021, Kolowski et al 2021, and our study contributes to this knowledge base in a novel way by demonstrating the nonlinear effects of terrain steepness on species-specific detection. Our results also support applying lure in camera viewsheds to increase the detection of carnivores.…”
Section: Speciesmentioning
confidence: 94%
“…Due to low levels of spatial patterning in animal detections between camera traps (Kolowski et al 2021), researchers have concluded it is problematic to assign detection of animal species at the fine spatial scale of a single camera‐trap viewshed to occurrence of that species at broad spatial scales (Evans et al 2019, Hofmeester et al 2021). However, in systems with high landscape complexity, accounting for the effects of topography on species detections (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We utilized images from camera traps that were deployed by the SCANDCAM project (viltkamera.nina.no), originally designed to monitor Eurasian lynx (Lynx lynx ) (Hofmeester et al 2021). Camera traps were deployed in multiple study areas in an extensive grid with approximately one camera per 50 km 2 grid cell (Figure 1).…”
Section: Data Collectionmentioning
confidence: 99%